ปัจจัยพยากรณ์พฤติกรรมสร้างสรรค์ของพยาบาลวิชาชีพโรงพยาบาลเอกชน กรุงเทพมหานคร - ปิยะรัตน์ พุ่มวิเศษ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purpose of this research were 1) to study innovative behavior of professional nurses 2) to analyze the relationships between self-efficacy, psychological empowerment, occupational stress and innovative behavior of professional nurses, and 3) to determine predictors of innovative behavior of professional nurses. Study samples were 299 professional nurses with at least 1 year experience, selected by multi-stage sampling from private hospitals accredited by Joint Commission International and located in Bangkok metropolis. The research instruments were Self-Efficacy Questionnaire (Bandura, 1997), Psychological Empowerment Questionnaire (Spreitzer, 1995), Occupational Stress Questionnaire (Wheeler and Riding, 1995) and Innovative Behavior Questionnaire (Kleysen and Street, 2001) All instruments were tested for content validity and reliability with Cronbach’s Alpha Coefficient of .83, .93, .85 and .90, respectively. The data were analyzed by percentage, mean, standard deviation, Pearson’s product moment correlation coefficients, and stepwise multiple regression analysis. Major findings were as follows: Innovative behavior of professional nurses was at a good level (¯("x" ) = 3.57, SD = .58). Self-efficacy and psychological empowerment were positively related to innovative behavior of professional nurses (r = .20 and .327 respectively, p < .05) while occupational stress was not related to innovative behavior of professional nurses. The variable predicting innovative behavior of professional nurses at p = .05 was psychological empowerment. This predictor accounted for 10.7 percent of the variance(R2= 10.7).The standardized equation was: Innovative behavior = .327 Psychological empowerment